2005
DOI: 10.1210/jc.2004-1843
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glucose Tolerance over Time in Women with Polycystic Ovary Syndrome: A Controlled Study

Abstract: We performed this study to access the changes in glucose tolerance over time in a group of women with polycystic ovary syndrome (PCOS) (n = 71) and control women (n = 23) with regular menstrual cycles and baseline normal glucose tolerance. Mean follow-up was between 2 and 3 yr for both groups (PCOS 2.5 ± 1.7 yr; controls 2.9 ± 2.1 yr). Based on World Health Organization glucose tolerance categories, there was no significant difference in the prevalence of glucose intolerance at follow-up in the PCOS group. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
1
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(171 citation statements)
references
References 30 publications
7
151
1
12
Order By: Relevance
“…It's possible that this increase in prevalence in the fourth decade of life can reflect the natural history of AGM in patients with PCOS. In fact, AGM, as categorized by WHO criteria, tends to worsen over time in women with PCOS, with a non-significant nearly 2-fold increase in the rates of conversion for subjects with PCOS and baseline normal glucose tolerance, without a concomitant change in BMI (16).…”
Section: Discussionmentioning
confidence: 99%
“…It's possible that this increase in prevalence in the fourth decade of life can reflect the natural history of AGM in patients with PCOS. In fact, AGM, as categorized by WHO criteria, tends to worsen over time in women with PCOS, with a non-significant nearly 2-fold increase in the rates of conversion for subjects with PCOS and baseline normal glucose tolerance, without a concomitant change in BMI (16).…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS are known to be at an increased risk for the development of IGT and T2DM, which is thought to be a direct consequence of the high prevalence of obesity and insulin resistance. Furthermore, in PCOS women with normal glucose tolerance, a conversion rate to an IGT of 16% per year has been reported (24). In addition to obesity and a positive family history of type 2 diabetes, other risk factors are being discussed to contribute to the high prevalence of insulin resistance and abnormal glucose metabolism in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported progression of 2% from normal glucose tolerance to DM in lean patients with PCOS followed up for 15 years (26). Only one early study reported increase in insulin levels (11), a finding not corroborated by the other available reports (23,24,25,26,27,28). The existing prospective studies assessing progression to DM in women with PCOS are summarized in Table 2 and emphasize the role of BMI in DM development.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%